Тенденції і виклики, пов’язані із станом довкілля й екологічними ризиками на сільських територіях, у продовольчому забезпеченні та землекористуванні України - Ібатуллін, Шаміль Ільдусович; Крупін, В. Є.; Сакаль, Оксана Володимирівна (НУБіП України, 2025)
Abstract The paper substantiates the cause-and-effect relationships and, employing the One Health approach, identifies negative trends in the impact of land use practices, agricultural production, climate change, biodiversity loss, and other anthropogenic factors on food security and access to land in the context of fundamental human rights. It highlights that war exacerbates ecological risks. The necessity of incorporating these risks into agrarian and rural development policies and implementing appropriate mitigation measures is substantiated.
Trends and challenges related to the state of the environment and ecological risks in rural areas, food supply, and land use in Ukraine
Keywords: сільські території; землекористування; екологія довкілля; rural areas; land use; environmental ecology